The effects of nickel chloride on papillary muscle contractility under normothermic and hypothermic conditions: Comparison of active and hibernating ground squirrels (Urocitellus undulatus) with Wistar rats. - Alexey S. Averin; Kenneth B. Storey; Miroslav N. Nenov (Journal of Thermal Biology, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

Soil microbial community responses to contamination with silver, aluminium oxide and silicon dioxide nanoparticles - C. F. McGee; S. Storey; N. Clipson; E. Doyle (Ecotoxicology, 2017)

Zircon record of fractionation, hydrous partial melting and thermal gradients at different depths in oceanic crust (ODP Site 735B, South-West Indian Ocean) - A. Pietranik; C. Storey; J. Koepke; S. Lasalle (Contributions to Mineralogy and Petrology, 2017)

Dispersal distances of aquatic insects: upstream crawling by benthic EPT larvae and flight of adult Trichoptera along valley floors - S. Elizabeth Graham; Richard Storey; Brian Smith (New Zealand Journal of Marine and Freshwater Research, 2017)
Dispersal is an essential process which influences the effects of stream restoration on aquatic insect communities, yet dispersal capabilities of many New Zealand taxa remain unknown. We estimated realised dispersal distances of New Zealand Ephemeroptera, Plecoptera, and Trichoptera taxa by benthic crawling and of Trichoptera by aerial flight in intermittent streams, which are recolonised after every dry period. Benthic crawling distances were not more than 200 m for most genera. In contrast, adult caddisflies were found up to 1500 m from permanent water, with at least one family carrying eggs the full distance. This suggests greater potential for insects to recolonise distant restored sites by aerial dispersal than by crawling. Our results are a first step towards identifying the dispersal pathways used by desired colonist taxa and the distances over which they can disperse. This information will improve our ability to design and implement effective restoration.

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Rheomorphic ignimbrites of the Rogerson Formation, central Snake River plain, USA: record of mid-Miocene rhyolitic explosive eruptions and associated crustal subsidence along the Yellowstone hotspot track - Thomas R. Knott; Marc K. Reichow; Michael J. Branney; David R. Finn; Robert S. Coe; Michael Storey; Bill Bonnichsen (Bulletin of Volcanology, 2016)

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

Biodiversity values of small headwater streams in contrasting land uses in the Auckland region - RG Storey; S Parkyn; MW Neale; T Wilding; G Croker (New Zealand Journal of Marine and Freshwater Research, 2011)
The biodiversity values of 12 small headwater streams (catchments mostly

Genetic structure of Melanotaenia australis at local and regional scales in the east Kimberley, Western Australia - R. D. Phillips; A. W. Storey; M. S. Johnson (Journal of Fish Biology, 2009)
The Kimberley region of Western Australia possesses a poorly studied freshwater fish fauna with high endemism in an aquatic landscape subject to monsoonal floods and dry season isolation. In the first population genetic study of freshwater fish in this region, the authors tested the effects of geographic barriers on genetic structure at multiple spatial scales in east Kimberley populations of the western rainbowfish, Melanotaenia australis , the most widespread and abundant species in the region. Based on allozyme comparisons, hierarchical analysis of F ST revealed increasing genetic subdivision with spatial scale. Minimal genetic structure within creeklines demonstrated that wet season dispersal, rather than dry season isolation, determines genetic structure at small scales. At the scale of sub‐catchments, a pattern of isolation by distance along creeklines was evident. Genetic subdivision between adjacent river systems was greater between rivers separated by a plateau than by lowlands. This implies greater connectivity of populations in lowland areas and may explain the greater similarity of the east Kimberly freshwater fish fauna with lowlands to the east than with the more rugged regions to the west. Similarly, greater connectivity between lowland populations may account for the on‐average larger distribution of lowland Melanotaeniids.

A multi‐scale segmentation approach to filling gaps in Landsat ETM+ SLC‐off images - S. K. Maxwell; G. L. Schmidt; J. C. Storey (International Journal of Remote Sensing, 2007)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Estrogen receptor-α and -β immunoreactivity and mRNA in neurons of sensory and autonomic ganglia and spinal cord - R.E. Papka; M. Storey-Workley; P.J. Shughrue; I. Merchenthaler; J.J. Collins; S. Usip; P.T.K. Saunders; M. Shupnik (Cell and Tissue Research, 2001)

Seasonal change and prolonged anoxia affect the kinetic properties of phosphofructokinase and pyruvate kinase in oysters - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 2000)

Discordant responses of mitogen-activated protein kinases to anoxia and freezing exposures in hatchling turtles - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 1999)

Fishes of floodplain habitats of the Fly River system, Papua New Guinea, and changes associated with El Niño droughts and algal blooms - Stephen Swales; Andrew W. Storey; Ian D. Roderick; Boga S. Figa (Environmental Biology of Fishes, 1999)

Suppression of reproductive development and longevity in the redshouldered leaf beetle,Monolepta australis (Col.: Chrysomelidae) by the tachinid,Monoleptophaga caldwelli (Dipt.) - H. A. C. Fay; R. I. Storey; S. G. Defaveri; J. D. Brown (BioControl, 1993)